Role of Neuromuscular Blocking Agents in Acute Respiratory Distress Syndrome: An Updated Meta-Analysis of Randomized Controlled Trials - Wei, Xue-biao; Wang, Zhong-hua; Liao, Xiao-long; Guo, Wei-xin; Qin, Tie-he; Wang, Shou-hong (Frontiers in Pharmacology, 2020)
Background: The therapeutic role of neuromuscular blocking agents (NMBA) in patients with acute respiratory distress syndrome (ARDS) remains controversial. Methods: We systematically reviewed randomized controlled trials investigating the use of NMBA in ARDS patients from inception to July 2019. Relative risk (RR) was calculated for the incidence of barotrauma and mortality using the random-effect or fixed-effect model according to heterogeneity analysis. Results: Data were combined from five randomized controlled trials that included 1461 patients (724 in the NMBA group and 737 in the control group). Pooled analysis showed that NMBA infusion did not reduce 28 day mortality (RR=0.72, 95% confidence interval (CI) 0.44 to 1.17, P=0.180, I-squared=62.8%), but was associated with lower intensive care unit (ICU) mortality (RR=0.60, 95% CI 0.41 to 0.88, P=0.009, I-squared=9.2%). In addition, the incidence of barotrauma was significantly lower in patients treated with NMBA (RR=0.53, 95% CI 0.33 to 0.84, P=0.007, I-squared=0). However, infusion of NMBA might increase the risk of ICU-acquired weakness (RR=1.34, 95% CI 0.97 to 1.84, P=0.066, I-squared=0). Conclusion: Infusion of NMBA could reduce ICU mortality and the incidence of barotrauma. The risk of ICU-acquired weakness was higher in moderate-to-severe ARDS patients treated with NMBA. The real effects of NMBA need to be further evaluated and confirmed by a study with a stricter design.